(untitled) (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research paper explores the critical significance of listening competence and comprehension in English for vocational learners, with a focus on their implications for workforce readiness and organizational success. Employing a descriptive qualitative literature review approach, the study delves into the multifaceted nature of these skills, their competence levels, basic needs, and the pressing urgency surrounding their development within the realm of vocational education. The findings of this research reveal that listening competence extends far beyond passive listening, encompassing the ability to discern specific information, identify main ideas, make inferences, and engage in critical listening. These diverse competence levels mirror the complexity of communication within the professional world. Moreover, the study highlights the fundamental needs of vocational learners, emphasizing the importance of access to diverse listening materials, interactive learning opportunities, and tailored language support programs. The urgency surrounding the development of listening competence and comprehension arises from the forces of globalization and technological advancement. English has become the universal language for international business and communication, making strong listening skills a prerequisite for effective cross-cultural engagement